Arylmalonate Decarboxylase‐Catalyzed Asymmetric Synthesis of Both Enantiomers of Optically Pure Flurbiprofen. Issue 5 (28th January 2016) - Gaßmeyer, Sarah Katharina; Wetzig, Jasmin; Mügge, Carolin; Assmann, Miriam; Enoki, Junichi; Hilterhaus, Lutz; Zuhse, Ralf; Miyamoto, Kenji; Liese, Andreas; Kourist, Robert
Abstract: The bacterial decarboxylase (AMDase) catalyzes the enantioselective decarboxylation of prochiral arylmalonates with high enantioselectivity. Although this reaction would provide a highly sustainable synthesis of active pharmaceutical compounds such as flurbiprofen or naproxen, competing spontaneous decarboxylation has so far prevented the catalytic application of AMDase. Here, we report on reaction engineering and an alternate protection group strategy for the synthesis of these compounds that successfully suppresses the side reaction and provides pure arylmalonic acids for subsequent enzymatic conversion. Protein engineering increased the activity of the synthesis of the ( S )‐ and ( R )‐enantiomers of flurbiprofen. These results demonstrated the importance of synergistic effects in the optimization of this decarboxylase. The asymmetric synthesis of both enantiomers in high optical purity (>99 %) and yield (>90 %) can be easily integrated into existing industrial syntheses of flurbiprofen, thus providing a sustainable method for the production of this important pharmaceutical ingredient. Abstract : Optically pure flurbiprofen : A novel deprotection strategy for the preparation of the starting material combined with decarboxylase (AMDase) variants optimized by enzyme engineering allowed the asymmetric synthesis of both enantiomers of the non‐steroidal anti‐inflammatory drug (NSAID) flurbiprofen in excellent yield and optical purity.